If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2x = 6x + -3 Reorder the terms: 5 + -2x = -3 + 6x Solving 5 + -2x = -3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + -2x + -6x = -3 + 6x + -6x Combine like terms: -2x + -6x = -8x 5 + -8x = -3 + 6x + -6x Combine like terms: 6x + -6x = 0 5 + -8x = -3 + 0 5 + -8x = -3 Add '-5' to each side of the equation. 5 + -5 + -8x = -3 + -5 Combine like terms: 5 + -5 = 0 0 + -8x = -3 + -5 -8x = -3 + -5 Combine like terms: -3 + -5 = -8 -8x = -8 Divide each side by '-8'. x = 1 Simplifying x = 1
| 2/3x0=5 | | 4(4x^2-20x+25)-(9x^2+6x+1)=0 | | x*10+30=x*6+126 | | 4=-2(1/2*-1) | | 5x+14=30-6x | | 4=-2(1/2*-1 | | 2.75x=.35x+12000 | | P=b+2a | | y=-2(x+2)(x-3) | | 2+10x=-25+x | | 0.5(5-7x)8-(4x+6)= | | 8t=2r+2s | | -20x-5y=-15 | | 4x-19=2x+3 | | 11+2x=6x-4 | | 7x+4=3+16 | | -20-5y=-15 | | 8s=(rt) | | 12xsquared+18x+6=0 | | 4x+12=21+2x | | 4x=12/7 | | 40=4/5y | | P=b+2a+3cfor | | 2*x^4+8*x^3+7*x^2-2*x-1=0 | | (x^2+2x-1)(2x^2+4x+1)=0 | | 4y-12x=20 | | 19.6x+156.8=58.8x+470.4 | | 3(f-10)=-51 | | 36r^3-49r= | | 10(s-4)=-137 | | 122-(7x+6)=7(x+8)+x | | (9x+10)+(2x+4)= |